2015
DOI: 10.3389/fmicb.2015.01352
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussis Isolates from Argentinean Whooping Cough Patients Display Enhanced Biofilm Formation Capacity Compared to Tohama I Reference Strain

Abstract: Pertussis is a highly contagious disease mainly caused by Bordetella pertussis. Despite the massive use of vaccines, since the 1950s the disease has become re-emergent in 2000 with a shift in incidence from infants to adolescents and adults. Clearly, the efficacy of current cellular or acellular vaccines, formulated from bacteria grown in stirred bioreactors is limited, presenting a challenge for future vaccine development. For gaining insights into the role of B. pertussis biofilm development for host coloniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 53 publications
1
25
0
1
Order By: Relevance
“…After 6 h from the start of the experiment, the oscillations continuously increased with time. This phenomenon could be associated with the beginning of replication of the adhered cells, since they are entering the exponential phase of growth, as we have previously reported for B. pertussis biofilm growth . Bacterial viability after attachment procedure was also assessed using fluorescent dyes (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…After 6 h from the start of the experiment, the oscillations continuously increased with time. This phenomenon could be associated with the beginning of replication of the adhered cells, since they are entering the exponential phase of growth, as we have previously reported for B. pertussis biofilm growth . Bacterial viability after attachment procedure was also assessed using fluorescent dyes (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 72%
“…We have previously assessed the growth kinetic of Bordetella pertussis , the etiological agent of whooping cough or pertussis, in both Stainer–Scholte (SS) liquid medium as planktonic cells, and adhered to surfaces as sessile populations forming biofilm . B. pertussis can adhere and live attached to different surfaces (polypropylene, glass) where it shows a specific growth rate ( µ ) of 0.03 h −1 .…”
Section: Introductionmentioning
confidence: 99%
“…This study found differences in the expression of ACV antigens between current clinical strains from California and Tohama I. Finally, Arnal et al and Dorji et al used 2D gels and isobaric tags for relative and absolute quantification (iTRAQ), respectively, to identify key differences in protein expression under biofilm forming conditions in current clinical strains against Tohama I. These differences correlated with faster biofilm formation in clinical strains.…”
Section: Introductionmentioning
confidence: 73%
“…Bacterial aggregates form in shaking culture and positively correlate with biofilm formation in many bacterial species (Sorroche et al ., ; Kragh et al ., ). Exogenous AC domain was added to growing cultures of B. pertussis and the aggregation index was determined at 24 hours, as previously described for B. pertussis (Arnal et al ., ). Exogenous AC domain decreased bacteria aggregation by 75% (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Ongoing studies support the concept that B. pertussis forms biofilm during infection; recent clinical isolates form more biofilm compared to a lab‐passaged isolate, BP338, and de Gouw et al . showed that biofilm‐derived antigens protect mice from B. pertussis infection (de Gouw et al ., ; Arnal et al ., ). The closely related animal pathogen, B. bronchiseptica forms biofilm in vitro on abiotic surfaces and biofilm formation contributes to its chronic infection of dogs and other mammals (Fenwick, ).…”
Section: Introductionmentioning
confidence: 97%